Expanding analytic possibilities in pediatric solid organ transplantation through linkage of administrative and clinical registry databases. (21st February 2019) - Godown, Justin; Hall, Matt; Thompson, Bryn; Thurm, Cary; Jabs, Kathy; Gillis, Lynette A.; Hafberg, Einar T.; Alexopoulos, Sophoclis; Karp, Seth J.; Soslow, Jonathan H.
Abstract: Database linkage is a common strategy to expand analytic possibilities. Our group recently completed a linkage between the SRTR and PHIS databases for pediatric heart transplant recipients. The aim of this project was to expand the linkage between SRTR and PHIS to include liver, kidney, lung, heart‐lung, and small bowel transplants. All patients (<21 years) who underwent liver, kidney, lung, heart‐lung, or small bowel transplant were identified from the PHIS database using APR‐DRG codes (2002‐2018). Linkage was performed in a stepwise approach using indirect identifiers. Hospital costs were estimated based on hospital charges and cost‐to‐charge ratios, inflated to 2018 dollars and described by transplant type. A total of 14 061 patients overlapped between databases. Of these, 13 388 (95.2%) were uniquely linked. Linkage success ranged from 92.6% to 97.8% by organ system. A total of 12 940 (92%) patients had complete cost data. Hospitalization costs were greatest for patients undergoing small bowel transplantation with a median cost of $734 454 (IQR $336 174 ‐ $1 504 167), followed by heart $565 386 (IQR $352 813 ‐ $999 216), heart‐lung $471 573 (IQR $328 523 ‐ 992 438), lung $303 536 (IQR $215 383 ‐ $612 749), liver $200 448 (IQR $130 880 ‐ $357 897), and kidney transplant $94 796 (IQR $73 157 ‐$131 040). We report a robust linkage between the SRTR and PHIS databases, providing an invaluable tool to assess resource utilization in solid organ transplant recipients. Our analysis provides contemporary cost data for pediatric solid organ transplantation from the largest US sample reported to date. It also provides a platform for expanded analyses in the pediatric transplant population.